Heavy metals, organic solvents, and multiple sclerosis: An exploratory look at gene-environment interactions. Issue 1 (2nd January 2016) - Napier, Melanie D.; Poole, Charles; Satten, Glen A.; Ashley-Koch, Allison; Marrie, Ruth Ann; Williamson, Dhelia M.
ABSTRACT: Exposure to heavy metals and organic solvents are potential etiologic factors for multiple sclerosis (MS), but their interaction with MS-associated genes is under-studied. The authors explored the relationship between environmental exposure to lead, mercury, and solvents and 58 single-nucleotide polymorphisms (SNPs) in MS-associated genes. Data from a population-based case-control study of 217 prevalent MS cases and 496 age-, race-, gender-, and geographically matched controls were used to fit conditional logistic regression models of the association between the chemical, gene, and MS, adjusting for education and ancestry. MS cases were more likely than controls to report lead (odds ratio [OR] = 2.03; 95% confidence interval [CI]: 1.07, 3.86) and mercury exposure (OR = 2.06; 95% CI: 1.08, 3.91). Findings of potential gene-environment interactions between SNPs in TNF- α, TNF- β, TCA-β, VDR, MBP, and APOE, and lead, mercury, or solvents should be considered cautiously due to limited sample size.